Current Role of Prospective Monitoring, Pre-emptive and Prophylactic Therapy for Human Herpesvirus-6 after Allogeneic Stem Cell Transplantation - Handley, Guy (Open Forum Infectious Diseases, 2022)
Human herpesvirus-6 (HHV-6) frequently reactivates after allogeneic stem cell transplantation (SCT). Most patients are asymptomatic and viremia often resolves without therapy; however, transplant related complications may be associated with reactivation. Multiple presentations have been attributed to HHV-6 reactivation after SCT including encephalitis. Several strategies have been trialed to reduce such risks or complications. Challenges exist with prospective monitoring strategies, and established thresholds of high-level reactivation may be limited. Three published guidelines and extensive trials focusing on pre-emptive and prophylactic strategies are reviewed. Future areas of investigation and high-risk populations are described. Existing trials and testing platforms have significant limitations, and to date no clear benefit for a pre-emptive or prophylactic intervention has been demonstrated.

Human herpesvirus 6 and central nervous system disease in oncology patients: A retrospective case series and literature review - Handley, Guy; Hasbun, Rodrigo; Okhuysen, Pablo (Journal of Clinical Virology, 2021)
Background Human herpesvirus 6 (HHV-6) can reactivate with immunosuppression and cause central nervous system (CNS) dysfunction. Much of the literature describes cases after hematopoietic stem cell transplantation (HSCT), ranging from encephalitis to a post-transplant acute limbic encephalitis syndrome (PALE). Outside of HSCT, studies of HHV-6 encephalitis are limited to case reports. Objectives This study was designed to review HHV-6 CNS infection, and evaluate all patients admitted to MD Anderson Cancer Center between March 2016 and December 2018 with detectable HHV-6 DNA in the cerebrospinal fluid (CSF). Study Design Patients with HHV-6 DNA detected in the CSF using the Viracor or Biofire® Meningitis Encephalitis Panel platforms and no other identified etiology were identified and demographic features, known risk factors, imaging findings, CSF analysis, treatments and patient outcomes were extracted from medical records. Results 725 patients underwent HHV-6 testing during the study timeframe, with 19 cases (2.6 %) of HHV-6 mediated CNS disease identified. Most patients, 13/19 (68 %), had undergone HSCT with median time to presentation of 31 days after transplant. Survival at 240 days after transplant was 62 %. CSF had lymphocyte predominance and nearly all patients had peripheral lymphopenia. Other at risk populations identified included patients who received chimeric antigen receptor (CAR) T-cell therapy and biologic immunotherapy. Notable discordance among testing platforms was found in 5/9 (55 %) instances. Conclusions In addition to HSCT patients, HHV-6 reactivation leading to CNS disease also occurs in settings such as following adoptive T cell therapy or biologic immunotherapy. Significant diagnostic discordance exists between testing platforms.
Keywords: Chimeric antigen receptor T-cell therapy; Encephalitis; Hematopoietic stem cell transplantation; Human herpesvirus 6; Post-Transplant acute limbic encephalitis

American Society for Transplantation and Cellular Therapy Series #9: Management of Human Herpesvirus 6B After Hematopoietic Cell Transplantation and Chimeric Antigen Receptor-T-Cell Therapy - Kampouri, Eleftheria; Handley, Guy; Phan, Tuan L.; Lee, Yeon Joo; Shaw, Ryan; Carpenter, Paul A.; Dadwal, Sanjeet S.; Chemaly, Roy F.; Papanicolaou, Genovefa A.; Ogata, Masao; Boeckh, Michael; Zerr, Danielle M.; et al. (Transplantation and Cellular Therapy, 2025)
The Practice Guidelines Committee and the Transplant Infectious Disease Special Interest Group of the American Society for Transplantation and Cellular Therapy developed guidelines focusing on human herpesvirus 6B (HHV-6B). A compendium-style approach was used to address a series of standalone frequently asked questions (FAQs), supported by tables and figures to spotlight key concepts. Adult and pediatric infectious disease and hematopoietic cell transplantation (HCT) content experts developed these FAQs and finalized recommendations after consensus was reached. This ninth topic in the series focuses on the relevant risk factors, diagnostic considerations, prophylaxis, and treatment approaches relevant to HHV-6B infections after HCT and chimeric antigen receptor-T-cell therapy.
Keywords: Allogeneic hematopoietic cell transplant; CAR-T-cell therapy; Encephalitis; HHV-6; Inherited chromosomally integrated HHV-6

Outcomes of Haploidentical Stem Cell Transplant Recipients With HHV-6B Reactivation - Handley, Guy; Yepes, Amanda; Eliassen, Eva; Dominguez, Gabriel; Pasikhova, Yanina; Klinkova, Olga; Baluch, Aliyah; Febres-Aldana, Anthony J; Alsina, Melissa; Elmariah, Hany; Khimani, Farhad; Hansen, Doris K; et al. (Open Forum Infectious Diseases, 2024)
Human herpesvirus 6B (HHV-6B) frequently reactivates following allogeneic stem cell transplant (alloHCT). Consensus guidelines note that haploidentical alloHCT may represent a high-risk population for which there is little evidence; this warrants further investigation.In this single-center retrospective study, we evaluated 188 consecutive adult patients receiving haploidentical alloHCT between 11/2014 and 11/2020 and compared outcomes between patients with HHV-6B reactivation receiving targeted antiviral therapy and those who were clinically observed.Of the 58 included patients, 21 (36.2%) received antiviral therapy for HHV-6B reactivation with foscarnet (n = 19) or ganciclovir (n = 2). There were no differences in patient or disease characteristics between treated and observed patients. Treated patients were more likely to have high-level DNAemia (85.7% vs 40.5%; P < .001) and had higher peak viral quantitative measurements (median log10, 4.65 vs 3.84; P < .001). The median time to clearance from plasma (interquartile range) was 13 (7.25–20.00) days for all patients and was not significantly different between groups. There were no differences in episodes of encephalitis, grade III/IV acute graft-vs-host disease (GVHD), or time to neutrophil or platelet engraftment among treated vs observed patients. Day 100 nonrelapse mortality was not significantly different in the multivariate analysis; however, the presence of central nervous system symptoms was strongly associated with worse survival (hazard ratio, 4.11; 95% CI, 1.27–13.34; P = .018).We did not observe a difference in clinical outcomes between the treated and observed groups of patients with HHV-6B reactivation following haploidentical alloHCT. With the rising use of haploidentical transplant and post-transplant cyclophosphamide GVHD prevention platforms, prospective studies are needed to further characterize the risk and outcomes associated with HHV-6B reactivation and therapy.